The Applied Linguistics and Peacebuilding in Colombian English Teachers’ Master’s Theses: A Focus on Criticality - Quintero-Polo, Alvaro; Guerrero-Nieto, Carmen Helena (Colombian Applied Linguistics Journal, 2025)
This article presents a review from a social and critical perspective of applied linguistics (AL) within English language teaching (ELT) and how it relates to the notion of education for peace in Colombia. The review involved a content analysis of 27 master's theses authored by English language teacher-researchers. The study was situated within the MA program in AL at a public university and focused on examining the interplay between the critical dimension of AL and education for peace in the schools where these teacher-researchers taught. For the authors of these theses, the classroom served as a social and political stage where they conducted their pedagogical and research initiatives reported in their theses. The selection of the 27 theses was based on the critical notion of peace as an issue relevant to the social and critical dimension of AL. The research question used for the review is: How do master's theses within the framework of critical AL written by English language teacher-researchers relate to education for peace? The review yielded valuable insights in the form of an emerging theme about the relevance of critical applied linguistics in local settings. It also demonstrated the key role language plays in education for peace in promoting conflict resolution and encouraging social awareness in local spaces.